HUBUNGAN TINGKAT PENGETAHUAN PETANI DENGAN EFEKTIVITAS PENGGUNAAN KARTU TANI DI DESA JRAGUNG, KECAMATAN KARANGAWEN, KABUPATEN DEMAK - Rizki Utami; Siwi Gayatri; Kadhung Prayoga (Universitas Galuh, 2023)
The “Kartu Tani” program is a government program to optimize subsidized fertilizer at the farmer level. Farmer did not understand on how to use “Kartu Tani”, forget the password and did not understand the benefits of having a “Kartu Tani”. This study were aims to analyze the farmers’ knowlegde and the effectiveness of using “Kartu Tani” and to analyze the relationship between farmers' knowledge and the effectiveness of using “Kartu Tani”. The research method used was a survey method. Determination of respondents was simple random sampling as many as 78 respondents. The data used were primary data and secondary. Data collection was done by interview and observation. Data analysis used were descriptive analysis and Spearman rank correlation. The results showed that farmers’ knowlegde was in moderate category and the effectiveness of using “Kartu Tani” was categorized as less effective. There was a weak and positive relationship between farmer’ knowledge and the effectiveness of using “Kartu Tani”, as well as having a correlation coefficient of 0.242. This was due to the lack of socialization and introduction of the program at farmer level. It ilustrate that it is necessary to provide in-depth and sustainable counseling program for farmers regarding the program of “Kartu Tani”.